ANALYSIS OF GENETIC VARIABILITY IN SOURSOP (Annona muricata L.) POPULATIONS FROM CENTRAL JAVA AND EAST JAVA BASED ON RANDOM AMPLIFIED POLYMORPHIC DNA (RAPD) MARKER - Suratman Suratman; Ari Pitoyo; Sri Mulyani (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2013)
The objective of this research was to determine genetic variability of the soursop (Annona muricata L.) populations from Central Java and East Java based on RAPD markers. Leaves of 40 individuals were collected from 4 soursop populations in Central Java and East Java, include : Sukoharjo, Karanganyar (Central Java), and Ngawi, Pacitan (East Java). Genomic DNA was extracted from the leaves by the CTAB extraction procedure with some modifications. A total of 15 RAPD primers were purchased from commercial source and tested to find specific diagnostic markers for each individuals by RAPD-PCR. The measurement of soursop population genetic distance was based on similarity coefficient using method of Group Average Clustering and Unweight Pair Group Method Arithmetic (UPGMA) of NTSYS program version 2.02i. Results showed that each soursop population collected from different localities seemed have variability in RAPD profiles by using different primers. Four RAPD polymorphic primer was selected from 15 RAPD primers, namely A18, A20, P10 and P11. A total of 58 bands produced, varying from 9 to 20 bands per primer. The selected four RAPD primers produced 57 polymorphic bands, whereas polymorphism for each primer ranged from 95 % to 100 %. Dendrogram indicated that four soursop populations tend to segregate form two separated clade. The sample collected from Sukoharjo formed a separate cluster while the sample collected from Ngawi, Pacitan and Karanganyar grouped together in other cluster and diverged from population Sukoharjo.